Associations of cereal grains intake with cardiovascular disease and mortality across 21 countries in Prospective Urban and Rural Epidemiology study: prospective cohort study. (3rd February 2021) - Swaminathan, Sumathi; Dehghan, Mahshid; Raj, John Michael; Thomas, Tinku; Rangarajan, Sumathy; Jenkins, David; Mony, Prem; Mohan, Viswanathan; Lear, Scott A; Avezum, Alvaro; Lopez-Jaramillo, Patricio; Rosengren, Annika; et al.
Abstract: Objective: To evaluate the association between intakes of refined grains, whole grains, and white rice with cardiovascular disease, total mortality, blood lipids, and blood pressure in the Prospective Urban and Rural Epidemiology (PURE) study. Design: Prospective cohort study. Setting: PURE study in 21 countries. Participants: 148 858 participants with median follow-up of 9.5 years. Exposures: Country specific validated food frequency questionnaires were used to assess intakes of refined grains, whole grains, and white rice. Main outcome measure: Composite of mortality or major cardiovascular events (defined as death from cardiovascular causes, non-fatal myocardial infarction, stroke, or heart failure). Hazard ratios were estimated for associations of grain intakes with mortality, major cardiovascular events, and their composite by using multivariable Cox frailty models with random intercepts to account for clustering by centre. Results: Analyses were based on 137 130 participants after exclusion of those with baseline cardiovascular disease. During follow-up, 9.2% (n=12 668) of these participants had a composite outcome event. The highest category of intake of refined grains (≥350 g/day or about 7 servings/day) was associated with higher risk of total mortality (hazard ratio 1.27, 95% confidence interval 1.11 to 1.46; P for trend=0.004), major cardiovascular disease events (1.33, 1.16 to 1.52; P for trend<0.001), and their composite (1.28, 1.15 to 1.42; P for trend<0.001) compared with the lowest category of intake (<50 g/day). Higher intakes of refined grains were associated with higher systolic blood pressure. No significant associations were found between intakes of whole grains or white rice and health outcomes. Conclusion: High intake of refined grains was associated with higher risk of mortality and major cardiovascular disease events. Globally, lower consumption of refined grains should be considered.